Sinergi Perguruan Tinggi Dalam Pendampingan Dosen Pemula Untuk Penulisan Artikel Ilmiah Bereputasi - Zulfikar; Iskandar, Syah; Ayunda, Desy Sary; Haekal, T.M; Muhammad, Muhammad (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2025)
The limited academic writing skills of early-career lecturers remain a major challenge in improving the quality and quantity of scientific publications in Islamic higher education institutions. This community service program aimed to enhance the ability to write Islamic-oriented scientific articles through collaboration between Universitas Islam Kebangsaan Indonesia (UNIKI) and the State Institute for Islamic Studies (IAIN) Takengon. The program involved 10 early-career lecturers who participated in a three-day offline training followed by two weeks of online mentoring. The method employed included intensive workshops, structured writing practice, and evaluative mentoring by senior lecturers. The results showed significant improvement, with 83% of participants able to produce articles that met the standards of nationally accredited journals. A total of 8 articles were successfully completed and submitted, with 5 articles accepted and published in SINTA 4-5 journals, while 3 others are still under review. This program also facilitated the formation of a cross-campus writing group committed to ongoing academic collaboration. These findings indicate that inter-institutional collaboration combined with a mentoring approach is effective in strengthening the scientific writing capacity of early-career lecturers in Islamic universities. Keywords: Collaboration, Early-Career Lecturers, Academic Writing, Publication, Islamic Higher Education Rendahnya kemampuan menulis ilmiah dosen pemula menjadi salah satu kendala dalam meningkatkan kualitas dan kuantitas publikasi di perguruan tinggi Islam. Program pengabdian ini bertujuan untuk meningkatkan keterampilan menulis artikel ilmiah berwawasan Islam melalui kolaborasi antara Universitas Islam Kebangsaan Indonesia (UNIKI) dan Institut Agama Islam Negeri (IAIN) Takengon. Kegiatan diikuti oleh 10 dosen pemula yang mengikuti pelatihan intensif selama tiga hari secara luring dan dilanjutkan dengan pendampingan daring selama dua minggu. Metode yang digunakan mencakup pelatihan, praktik menulis artikel secara bertahap, serta mentoring evaluatif oleh dosen senior. Hasil program menunjukkan peningkatan signifikan, di mana 83% peserta mampu menyusun artikel sesuai standar jurnal nasional terakreditasi. Sebanyak 8 artikel berhasil ditulis dan diajukan, dengan 5 artikel telah diterima dan terbit di jurnal SINTA 4-5, sementara 3 artikel lainnya masih dalam proses review. Program ini juga menghasilkan kelompok penulis lintas kampus yang berkomitmen melanjutkan kolaborasi akademik. Temuan ini menunjukkan bahwa kolaborasi antarinstitusi dengan pendekatan mentoring efektif dalam meningkatkan kapasitas penulisan ilmiah dosen pemula di lingkungan perguruan tinggi Islam. Kata kunci: Kolaborasi, Dosen Pemula, Penulisan Ilmiah, Publikasi, Perguruan Tinggi Islam